Student-Led discharge counseling program for High-Risk medications in a teaching hospital in Saudi Arabia: A pilot study - Ghada Bawazeer; Ibrahim Sales; Afnan Alsunaidi; Sarah Aljahili; Mohammad H. Aljawadi; Haya M. Almalag; Hadeel Alkofide; Mansour Adam Mahmoud; Fakhr Alayoubi; Majda Aljohani (Elsevier, 2021)
Discharge counseling by pharmacists reduces adverse medication events, emergency department visits, and readmissions. Studies indicate that pharmacy students in advanced pharmacy practice experiences (APPE) can deliver effective medication-related activities. An open label randomized controlled trial was conducted in adults discharged on warfarin, insulin, or both. Pharmacy students performed medication reconciliation, structured medication counseling, and follow-up calls 72-hours post-discharge. The usual care arm received traditional education. The primary outcome was the 30-day readmission rate post-discharge. Ninety-eight patients on high-risk medications were randomized to intervention (n = 51) or usual care (n = 47). The 30-day hospital readmission rate was lower in the intervention group (8/51, 15% vs. 11/47, 23%); (p = 0.48). There was no statistical difference in the time to first unplanned health care use (hazard ratio = 0.49 (95 %CI, 0.19-1.24), or the time-to-first clinic visit post-discharge (p = 0.94) between the two arms. Students identified 26 drug-related problems during reconciliation. Patients in the intervention arm reported high satisfaction with the service (mean 3.94; SD 0.11). Involving APPE students in the transition of care activities presents an excellent opportunity to minimize pharmacists' workload while maintaining patient care services.